PENGARUH KUALITAS PRODUK, KEMUDAHAN, DAN FAKTOR EMOSIONAL TERHADAP KEPUASAN PELANGGAN (STUDI KASUS DI KLINIK KOPI DUSUNSINDUHARJO KECAMATAN NGAGLIK KABUPATEN SLEMAN) - Wulandari, Fernanda; Widowati, Indah; Budiarto, Budiarto (Jurnal Dinamika Sosial Ekonomi, 2017)
The purpose of this research is (1) to analyze customer satisfaction based on suitability between performance and importance of the product at Klinik Kopi and (2) to analyze the influence of quality product, efficiency, and emotional factor on customer satisfaction at Klinik Kopi. The research method of this research uses a descriptive method. The method of conducting research uses a case study method. The method for acquiring the respondent in this research is accidental sampling method with the amount of the respondents is 40. For data collection this research uses interviews, questionnaires and observations. The result of the research showed that (1) customers are satisfied based on suitability between performance and importance of the product at Klinik Kopi (2) quality product, efficiency, and emotional factor has an influence on customer satisfaction at Klinik Kopi.Â Keywords: Quality product, efficiency, emotional factor, customer satisfaction, Klinik Kopi.